1986
DOI: 10.1083/jcb.103.6.2659
|View full text |Cite
|
Sign up to set email alerts
|

Distinct molecular interactions mediate neuronal process outgrowth on non-neuronal cell surfaces and extracellular matrices.

Abstract: Abstract.We have compared neurite outgrowth on extracellular matrix (ECM) constituents to outgrowth on glial and muscle cell surfaces. Embryonic chick ciliary ganglion (CG) neurons regenerate neurites rapidly on surfaces coated with laminin (LN), fibronectin (FN), conditioned media (CM) from several non-neuronal cell types that secrete LN, and on intact extracellular matrices. Neurite outgrowth on all of these substrates is blocked by two monoclonal antibodies, CSAT and JG22, that prevent the adhesion of many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
183
1
1

Year Published

1990
1990
2000
2000

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 242 publications
(201 citation statements)
references
References 65 publications
16
183
1
1
Order By: Relevance
“…4). This is similar to what has been observed previously for LN on tissue culture plastic, using these same neurons (Tomaselli et al, 1986). The potency of N-cadherin in our experiments compares favorably with the ability of the calcium-independent adhesion molecules, L1 and N-CAM, to stimulate growth.…”
Section: Purified N-cadherin Is An Inducer Of Process Outgrowthsupporting
confidence: 77%
See 3 more Smart Citations
“…4). This is similar to what has been observed previously for LN on tissue culture plastic, using these same neurons (Tomaselli et al, 1986). The potency of N-cadherin in our experiments compares favorably with the ability of the calcium-independent adhesion molecules, L1 and N-CAM, to stimulate growth.…”
Section: Purified N-cadherin Is An Inducer Of Process Outgrowthsupporting
confidence: 77%
“…Previous experiments have shown that neurons of the chick CG do not grow neurites on noninducing substrates like tissue culture plastic or poly-o-lysine, at least during the first 16-20 h of culture (e.g., Tomaselli et al, 1986). This is true despite the ability of the CG neurons to adhere to these substrates and extend lamellipodia.…”
Section: Purified N-cadherin Is An Inducer Of Process Outgrowthmentioning
confidence: 65%
See 2 more Smart Citations
“…The most well-studied examples of extrinsic factors are those derived from glial cells. Descriptive studies and both in vivo and in vitro manipulations indicate that neuron-glia interactions influence the generation and elaboration of neurites and provide a preferred substrate for neurite extension (Noble et al, 1984;Fallon, 1985;Tomaselli et al, 1986Tomaselli et al, , 1988Neugebauer et al, 1988;Smith et al, 1990;Norris and Kalil, 199 I;Baird et al, 1992).…”
mentioning
confidence: 99%